Media Frames of Climate Justice in China - Cheng, Yan; Justus Liebig University Giessen (My University, 2025)
This study examines how Chinese newspapers frame climate justice. It asks what media frames appear, how media outlets differ, and what social and political implications emerge. Using a multidisciplinary framework and critical discourse analysis, the study finds that Chinese media mainly reflect elite discourses, stressing climate diplomacy, distributive justice, historical responsibility, per capita emissions, and the right to development. China insists on these principles while cooperating internationally, especially on technology transfer and carbon intensity reductions. Energy security is central to its position, shaped by cultural and historical factors. China’s global identity remains ambiguous, shifting between developing nation and responsible major power. While frames are similar, market-oriented media take more bottom-up views. The study calls for a cosmopolitan approach, highlighting individual agency and the media’s potential to advance climate justice discourse.
Keywords: media frames; climate justice; climate change; China; ddc:300; ddc:070; ddc:400; ddc:320; ddc:100